Upaya Meningkatkan Kemampuan Literasi Dasar Siswa Melalui Pendekatan TaRL dengan Media Buku Bergambar - Nia, Lailatul Kurniati; Husniati; Kaninta, Novianti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve the literacy skills of first-grade students at SDN 50 Cakranegara. The method used was Classroom Action Research (CAR), conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection, to gradually enhance the quality of learning. Student participation was assessed through classroom observations, while learning outcomes were evaluated using tests administered at the end of each cycle. The research subjects were 10 students, comprising 6 boys and 4 girls. The findings indicate that the use of picture books as a complementary learning medium was successful. The average score during the pre-cycle was 66%, with 50% of students achieving mastery and 50% not yet achieving it. In Cycle I, the average increased to 72.5%, with 80% of students achieving mastery and 20% not yet. In Cycle II, the average rose further to 78.5%, with 90% of students achieving mastery and only 10% not yet achieving it. These results demonstrate that the teacher’s performance in implementing learning activities using picture book media was effective. Based on the results from the pre-cycle, Cycle I, and Cycle II, students’ reading abilities showed improvement after the application of picture book media. The researcher decided not to proceed to the next cycle as the study had met the minimum completion criterion of ≤76% and produced satisfactory outcomes.